Beneficial effects of Stevioside on AGEs, blood glucose, lipid profile and renal status in streptozotocin-induced diabetic rats - Aswar, Urmila; Gogawale, Vinayak; Miniyar, Pankaj; Patil, Yugendra (Journal of Applied Biomedicine, 2019)
The advanced glycated end products (AGEs) are formed in the diabetic patients; it is a major cause of macrovascular and microvascular complications in diabetes. Clinically there is no treatment available for the AGEs. Stveoside (Stv), a sweetener has potent anti-diabetic and anti-oxidant activity. Hence, we investigated its use in prevention of AGEs formation using in vitro and in vivo models. Diabetes was induced by streptozotocin (STZ). These rats were kept without treatment till blood HbA1c was markedly increased. They were then divided into 5 groups and treated orally with vehicle or Metformin (MET) or Stv respectively for 28 days. Every 7th day, animals were tested for body weight and blood glucose (BG). On the last day of treatment, all the groups were evaluated for physiological and biochemical parameters, histopathology and AGEs; N-carboxymethyl-lysine (CML) estimation. Stv showed inhibition of AGEs in in vitro as well as in in vivo respectively. Positive effects were seen on the BG, lipid profile and urine parameters as well it showed reduced formation of CML. It also showed antihyperglycaemic, antihyperlipedemic and nephroprotective activities. The present study provides scientific rationale for the use of Stv as a sweetener with additional benefits in diabetes.
Keywords: AGEs; Diabetes; Diabetes complications; N-carboxymethyl-lysine; Stevioside; Streptozotocin

Recursive partitioning analysis and anti-tubercular screening of 3-aminopyrazine-2-carbohydrazide derivatives - Miniyar, Pankaj; Mahajan, Anand; Anuse, Dattatray; Kumar, Ashish; Barmade, Mahesh; Sarkar, Dhiman; Arkile, Manisha; Khedkar, Vijay (Letters in Drug Design & Discovery, 2019)
Background: Treating tuberculosis is a challenge due to the development of drug resistance. Hence, it is imperative to develop novel leads having high potency and efficacy to curb drug resistance. Methods: The present research work is focused on microwave-assisted synthesis of novel twenty-six 3-amino-N'-benzylidenepyrazine-2-carbohydrazide derivatives (3a-z), where, lyophilization technique was used for isolation of the major intermediate, 3-aminopyrazin-2-carbohydrazide. All synthesized compounds were subjected for anti-tubercular screening against Mycobacterium tuberculosis H37Ra by using XTT Reduction Menadione Assay (XRMA) protocol. Results: Out of 26 synthesized compounds, four N'-substitutedbenzaldehyde-3-amino-pyrazine-2-carbohydrazide derivatives viz. 3i, 3j 3v and 3z showed significant activity against M. tuberculosis H37Ra. The compounds 3i, 3j, 3v and 3z showed 99, 98, 92 and 87 % inhibition respectively as compared to 94% inhibition shown by the standard drug rifampicin. The MIC and IC50 values were in the range of 24.3-110 and 5.9-20.8 mu g/ml respectively. Conclusion: A classification model called Recursive Partitioning (RP) based on binary Quantitative Structure-Activity Relationship (QSAR) was derived for the establishment of structure-activity relationship (SAR). The predictions derived on the basis of RP model were found to be in agreement with anti-tubercular screening data.
Keywords: 3-aminopyrazine; anti-tubercular activity; Carbohydrazide; lyophilization; QSAR; recursive partitioning